Some Attitudes Towards Retirement among Middle-Aged Employees - Crawford, Lawrence; Matlow, Jean (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1972)
The Ontario Longitudinal Study of Aging 1959-1978 interviewed 1,214 male employees at ages 48 and 54 on attitudes towards retirement, a suitable retirement age and views on not working. Replies at both ages are examined as well as some of the conditions which may have influenced attitudes towards retirement at age 54. Chi-square analysis indicated more employees were favourably disposed to retirement at age 54 than at the earlier age. Income level alone, of four factors studied, was positively related to attitudes towards retirement.